Dark optical and other soliton solutions for the three different nonlinear Schrodinger equations - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa (Springer, 2017)
In this work, the dark optical and singular soliton solutions of three different nonlinear Schrodinger equations (NLSE) are analyzed using Ricatti-Bernoulli (RB) sub-ODE method. We obtain new solutions that, in our opinion, are not known yet. The constraint conditions between the soliton parameters are determined. The obtained solitons may be used to explain and understand the physical nature of the wave spreads in the most dispersive optical medium.
Keywords: NLSE; RB sub-ODE method; Optical solitons